Index of political instability in brazil, 1889-2009 - Jaime Jordan Costantini; Mauricio Vaz Lobo Bittencourt (CEPAL Review, 2014)
This article aims to develop an index of political instability (ins) in Brazil between 1889 and 2009, reflecting a wide-ranging set of multiple phenomena that represent conflicts between the different social groups. By presenting different definitions of what is understood by political instability in the economics literature and by using multiple historical eventscoups détat, civil conflicts, constitutional or unconstitutional overthrow and changes in the composition of 50% of the ministerial cabinet different indicators are obtained which are then synthesized into a single index using the principal component technique, to obtain an ins for Brazil between 1889 and 2009.